Manipulating Electrocatalysis using Mosaic Catalysts. Issue 5 (14th May 2021) - Luo, Yuting; Chiang, Sum Wai; Tang, Lei; Zhang, Zhiyuan; Yang, Fengning; Yu, Qiangmin; Ding, Baofu; Liu, Bilu
Abstract : Mosaic Catalyst Strategy A mosaic catalyst strategy is developed by Bilu Liu and co‐workers, described in article number 2000059, to improve the activity of electrocatalysts by engineering their spatial structures, where the catalysts spread on conductive support with certain spatial structures, like chessboard. The local electric field on the electrode‐electrolyte interface, as well as the mass transfer ability of catalysts can be modulated by the mosaic catalyst strategy.